1994
DOI: 10.1159/000187982
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Erythropoietin Level during Azathioprine Treatment in Renal Transplant Recipients

Abstract: One hundred and six renal transplant patients were studied. During the first 12 months after renal transplantation all patients were treated with cyclosporine (Cy) and prednisone. At 12 months after transplantation the patients were randomly allocated to either conventional treatment with azathioprine (Az) and prednisone (group Az) or to continued treatment with Cy and prednisone (group Cy). Serum erythropoietin (s-EPO), glomerular filtration rate (GFR) and hematocrit (Hct) were measured at 12,18 and 24 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
(7 reference statements)
0
12
2
Order By: Relevance
“…Previous in vitro investigations involving cyclosporine have demonstrated concentrationdependent inhibition of erythropoietin release and proliferation of hematopoietic stem and progenitor cells (35,38). Azathioprine has been postulated to interfere with erythroid proliferation and erythropoietin receptor expression or interaction resulting in alterations to erythropoietin sensitivity (37). This study identified azathioprine-treated renal transplant patients possessing a nonfunctional TPMT mutant allele with significantly elevated cyclosporine whole blood trough concentrations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous in vitro investigations involving cyclosporine have demonstrated concentrationdependent inhibition of erythropoietin release and proliferation of hematopoietic stem and progenitor cells (35,38). Azathioprine has been postulated to interfere with erythroid proliferation and erythropoietin receptor expression or interaction resulting in alterations to erythropoietin sensitivity (37). This study identified azathioprine-treated renal transplant patients possessing a nonfunctional TPMT mutant allele with significantly elevated cyclosporine whole blood trough concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…Cyclosporine has been associated with stimulatory effects on bone marrow and early erythroid progenitors and has shown an inhibitory effect on erythroid progenitors and epoietin secretion (34)(35)(36)(37)(38). Previous in vitro investigations involving cyclosporine have demonstrated concentrationdependent inhibition of erythropoietin release and proliferation of hematopoietic stem and progenitor cells (35,38).…”
Section: Discussionmentioning
confidence: 99%
“…After kidney transplantation, red-cell production is related to the ability of the graft to release EPO and the potential of bone marrow progenitor cells to respond to the circulating hormone. Immunosuppres sive drugs used in renal transplantation may affect both processes: azathioprine (Aza) possesses a well-known suppressive effect on the bone marrow and in a recently published paper, Jensen et al [2] suggested that this might cause a compensatory increase in EPO production. Clinical observations as well as in vivo and in vitro experimental studies showed that cyclosporine (CsA) impaired EPO response to hypoxia [3][4][5], On the other side.…”
Section: Does Erythropoietin Production After Renal Transplantation Dmentioning
confidence: 99%
“…Studies of serial erythropoietin levels have shown that levels fall during periods of graft rejection, though it is not clear whether the severity of graft rejection correlates with the decrease in level [19]. Some patients prove resistant to rHuEPO therapy following rejection of a graft, with the underlying mechanism possibly involving inflammation in the retained graft, although the precise pathophysiology is not understood [20].…”
Section: Discussionmentioning
confidence: 99%